A Critical Study of Violence Against Women in the Perspective of Islamic Education - Ahmad Salim (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Violence against women (VAW) is a global issue rooted in historical, social, and cultural structures. This study critically examines the causes, impacts, and responses to VAW through feminist perspectives, legal frameworks, and social movements. It explores how gender-based violence persists due to patriarchal norms, economic disparities, and systemic inequalities. Additionally, the research highlights how religious interpretations influence perceptions of gender roles, with a particular focus on Islamic education. From an Islamic perspective, VAW contradicts the principles of justice, equality, and compassion embedded in the Qur’an and Hadith. However, cultural misinterpretations often obscure these teachings, leading to practices that perpetuate gender-based oppression. Islamic education plays a crucial role in shaping societal attitudes by promoting gender justice and educating communities about women’s rights. Through an inclusive and holistic curriculum, Islamic educational institutions can challenge patriarchal norms and cultivate a culture of non-violence. This study emphasizes that combating VAW requires a multidimensional approach, integrating legal measures, social interventions, and educational strategies. Strengthening Islamic education as a means of fostering ethical awareness and respect for women’s rights can contribute significantly to reducing violence and promoting gender equity.